PENERAPAN PENDEKATAN TEACHING AT THE RIGHT LEVEL (TaRL) UNTUK MENINGKATKAN HASIL BELAJAR PESERTA DIDIK DALAM PEMBELAJARAN SOSIOLOGI KELAS XI F4 DI SMA ADABIAH 2 PADANG - Azzahra, Salsabilla; Erningsih; Wibi Wijaya (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This research was motivated by the low learning outcomes of grade XI F4 students in Sociology at Adabiah 2 High School, Padang. The purpose of this study was to improve student learning outcomes using the Teaching at the Right Level (TARL) learning approach. The research method used was Classroom Action Research (CAR) formulated by Ari Kunto, which consists of four components: (1) Planning, (2) Action, (3) Observation, (4) Reflection, using a mixed methods approach. The research data consisted of information about the results of the actions obtained from observations of teacher activities and student learning outcome tests. This research was conducted in two cycles. The results of the first cycle of research showed that the average student learning outcome score remained around 70.6, with only 39.5% completing tasks and 59.9% not completing tasks. In the second cycle, student learning outcomes increased to an average of 84.8, with 83.5% completing tasks and a decrease of 16.6% not completing tasks. This indicates an improvement in learning outcomes, as seen in the second cycle, with an increase in average student scores. This demonstrates that learning outcomes improve with the use of the TaRL approach in sociology.